ANALISIS KESTABILAN LERENG TIMBUNAN OVERBURDEN : STUDI KASUS DESA KAMPUNG BARU KECAMATAN CEMPAKA BANJARBARU - Lucky Haryanto; Susanto Basuki (Universitas Lambung Mangkurat, 2006)
Coal mining, especially coal surface mining, requires a huge tracks of land to be disturbed. This disturbance includes removing vegetation, moving overburden (waste rock and soil), removing of coal and relocating overburden to backfill. The main environmental problems associated with land disturbance include erosion of the soil, dust pollution and losses of natural vegetation. Minimizing these impacts and rehabilitating land to a previous condition before mining now become requirements in most countries, including Indonesia. However, among small corporate mining, there is often poor adherence to the law because the lack of financial resources, ignorance of the law, poor mine management, and low level of expertise.Observation and slope stability analyses of disposal site have been conducted in Kampung Baru area ofBanjarbaruCity. The Stability analyses were carried out using the limit equilibrium computer program SLOPE-W (GEO-SLOPE International). In this program systematic search is performed to obtain the minimum factor of safety from a number of potential slid surfaces. Factors of safety were computed using Bishop’s method analyses.The result of slope stability analyses using SLOPE-W software shown that the existing condition of bench is not safe. To minimize the failure potential, this bench (single bench) should modified to be three-step-bench. The dimension of each step of bench should be arrange as follows: width of bench = 5 meters, height of bench = 5 meters, and angle of slope = 36o.